Development of resource-saving technologies in the dairy industry - Mykhalevych, Artur; Polishchuk, Galyna; Bass, Oksana (My University, 2021)
Development and implementation of resource-saving technologies at dairy industry enterprises of Ukraine is a modern direction of production sustainable development and economically profitable investment, which not only saves raw materials, but also affects the growth of production and reduces the negative impact on the environment.
Keywords: development; resource-saving technologies; the dairy industry; розроблення; ресурсозберігаючі технології; молочна промисловість; кафедра технології молока і молочних продуктів